The Influence of Service Quality, Brand Image, and Product Innovation on Guitar Customer Loyalty at PT Genta Tri Karya - Yayu Sri Rahayu; Hetty Kurniati; Musafa (Islamicate Institute, 2020)
Customer Loyalty is one of the crucial factors in increasing and decreasing sales within a company. Through the quality of service, brand image, and useful product innovation, the company is expected to increase customer loyalty, so it is expected to increase the company's sales. This study aims to determine the effect of service quality, brand image, and product innovation on the customer loyalty of Guitar Genta at PT Genta Tri Karya. The research method used was a survey method with descriptive and verification research types. The data used are primary data obtained from distributing questionnaires. The results showed that service quality is partially positive and not significantly affecting customer loyalty. Brand image is partially positive and not significant, and product innovation has a positive and significant effect on customer loyalty. However, service quality, brand image, and product innovation simultaneously have a positive and significant impact on the loyalty of Guitar Genta customers at PT Genta Tri Karya.